PENGARUH KEPEMIMPINAN KEPALA DESA TERHADAP EFEKTIVITAS PELAYANAN PADA MASYARAKAT MENURUT OTONOMI DESA BERDASARKAN UNDANG-UNDANG NO 6 TAHUN 2014 DAN PERAN PEMERINTAH DALAM PEMBANGUNAN DESA DI KABUPATEN SEKADAU KALIMANTAN BARAT - Genopepa Sedia (Universitas Kapuas Sintang, 2018)
The main task of the Village government is to carry out part of the authority of the subdistrict as a mandate given by the constitution and carry out other tasks based on applicable regulations. There are several inhibiting factors, but such things can still be anticipated by the government, which in this case is the head of the village or as another old law through motivations that are delivered directly and always increase the effectiveness of work and every government apparatus.